The renewal of social democracy and the „third way” of the British Labour Party - Havas Peter (Međunarodni Problemi)
The author tries to enlighten and analyse the current processes in the European Social Democracy intending to renew its strategy and doctrine and adapt it to the new economic, political and social challenges. He devotes special attention to the attempts of the British Labour Party to modernise itself and create a new doctrinal approach, the so-called third way. The author analyses the history of the New Labour and characteristics of the Tony Blair-led party, elaborating in detail the contents of the third way. The main conclusion he makes is that, in spite of the New Labour’s success at the two last general elections in Britain and the positive lessons to be drawn from the third way, it does not mean that all Social Democratic Parties should follow that example, for different social conditions demand different strategies and policies and relevant responses by every party.